Empirical Analysis of Street Safety: Driver Behavior and Traffic Characteristics on Traffic Accidents in Semarang - Dewa, Adenanthera (LifeSciFi, 2023)
Transportation issues are a common challenge faced by both developed and developing countries, including Indonesia. The transportation sector's primary goal is to establish a system that facilitates smooth, safe, fast, cost-effective, comfortable, and environmentally friendly movement of people, vehicles, and goods. In accordance with Law No. 22 of 2009 on traffic and road transportation, traffic accidents are defined as unexpected, non-intentional incidents occurring on the road involving vehicles, with or without other road users, resulting in human casualties and/or property damage. This research aims to assess the influence of driver behavior, intersection traffic characteristics, and traffic sign violations on traffic accidents at the Tlogosari Intersection in Semarang. The problem formulation, research objectives, and hypotheses in this study intend to analyze the positive and significant effects, both individually and collectively, of the independent variables on the dependent variable (traffic accidents). The study's subjects comprise motor vehicle users at the Tlogosari intersection in Semarang, with primary and secondary data serving as data sources. The study sample consists of 100 respondents who are Tlogosari Intersection users in Semarang, selected through non-probability sampling using the Incidental Sampling method. The data analysis technique employed is multiple linear regression analysis.